Influence of zeolite-organic mineral fertilizer on the enzyme activity of soil under rice (Eurasian Journal of Ecology, 2016)
To determine the effectiveness of zeolite-organic mineral fertilizer pilot experiments with the culture of rice varieties Marjane are carried out. Dehydrogenase, polyfenoloxidase and peroxidase activities of soil under rice before sowing, in the tillering phase and after harvest are defined. The results showed that the introduction of zeolite-organic mineral additives promoted increase in enzyme activity and reduce the rate of dehumification of soil under rice, as evidenced by the performance of the nominal factor of humification, which were higher by 13,3-26,8%, compared to the control.
Keywords: zeolite; organic mineral fertilizer; dehydrogenase; polyphenoloxidase; peroxidase; nominal factor of humification